2005
DOI: 10.1021/jp051229+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thermally Stable Highly Ordered Nanoporous Tin Oxide Thin Films with a 3D Face-Centered Orthorhombic Nanostructure

Abstract: Thin films of nanoporous tin oxide with a 3D face-centered orthorhombic nanostructure have been synthesized by self-assembly that is controlled by post-coating thermal treatment under controlled humidity. In contrast to the conventional evaporation-induced self-assembly (EISA), the films here have no ordered nanostructure after dip-coating. However, the initial coatings are formed under conditions that inhibit significant hydrolysis and condensation for extended periods. This allows the use of postsynthesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 20 publications
2
72
1
Order By: Relevance
“…In the wet chemical synthesis of the precursor, Pluronic F-127, a triblock copolymer was used as the structure direct agent for the nano-engineering of SnO 2 [15,[36][37][38]. By controlling its mole fraction, the porosity of the SnO 2 is controlled on the tens-of-nanometers scale to tailor the refractive index of the nano-material.…”
Section: Resultsmentioning
confidence: 99%
“…In the wet chemical synthesis of the precursor, Pluronic F-127, a triblock copolymer was used as the structure direct agent for the nano-engineering of SnO 2 [15,[36][37][38]. By controlling its mole fraction, the porosity of the SnO 2 is controlled on the tens-of-nanometers scale to tailor the refractive index of the nano-material.…”
Section: Resultsmentioning
confidence: 99%
“…Tolbert and coworkers, [18] Urade and Hillhouse, [7] and Grosso et al [11a] had already pointed out that a careful and well-chosen temperature program is needed to avoid mesostructural collapse during thermal treatment of Pluronic F127-derived SnO 2 and TiO 2 mesoporous films. These difficulties in the preparation of SnO 2 films could now be overcome by the superior templating properties of an appropriate structure-directing agent.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The most significant progress was recently achieved by Urade and Hillhouse, [7] who demonstrated that SnO 2 films with high mesopore regularity can be obtained by using Pluronic templates. This procedure involved a complex Crack-free, mesoporous SnO 2 films with highly crystalline pore walls are obtained by evaporation-induced self-assembly using a novel amphiphilic block-copolymer template ("KLE" type, poly(ethylene-co-butylene)-block-poly(ethylene oxide)), which leads to well-defined arrays of contracted spherical mesopores by suitable heat-treatment procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Hillhouse et al successfully removed the surfactants from mesostructured tin oxide films prepared through the water-vapor treatment. 451 By careful thermal treatment, consisting of heating at temperatures ranging from 50 to 250°C with a 30°C step and a 12 h pause at each temperature, a highly ordered mesoporous tin oxide film with a 3D face-centered orthorhombic nanostructure was obtained.…”
Section: Mesoporous Non-siliceous Filmsmentioning
confidence: 99%